Mentoring and job satisfaction in Malaysian SMEs - Lo, May-Chiun; Ramayah, T. (Emerald Publishing Limited, 2011)
Purpose – Building on social exchange theory, this paper aims to hypothesize the direct impact of mentoring on employees’ job satisfaction. Design/methodology/approach – A survey method was used to gather the information that was required in this study to examine the relationship between mentoring and employees’ job satisfaction among employees from small and medium enterprises in Malaysia. A total of 200 questionnaires were sent out to executives of the middle and lower management level from the 21 selected small and medium enterprises. A total of 156 Malaysian executives participated. Findings – The results show that there was a positive relationship between career mentoring and all dimensions in job satisfaction such as co-workers, job itself, promotion and supervisors. On the other hand, no significant relationship was found between psychosocial mentoring and three aspects of employees’ job satisfaction, namely co-workers, job itself, and promotion. Practical implications – This study has helped to establish a foundation for the study of job satisfaction and mentoring. The foundation established has generated more knowledge and arguments on mentoring in the workplace to enhance performance. This paper contributes to the literature on the relationship between mentoring and employees’ job satisfaction. Originality/value – Considering the potential cascading effect that a good relationship can have on subordinates’ job satisfaction, the paper shows that previous researches may have underestimated the impact of mentoring on job satisfaction.